Safety and efficacy of dimethyl fumarate in ALS: randomised controlled study. Issue 10 (3rd September 2021) - Vucic, Steve; Henderson, Robert D.; Mathers, Susan; Needham, Merrilee; Schultz, David; Kiernan, Matthew C.; ,
Abstract: Objective: Neuroinflammation is an important pathogenic mechanism in amyotrophic lateral sclerosis (ALS), with regulatory T cells (Tregs) mediating a slower rate of disease progression. Dimethyl fumarate enhances Treg levels and suppresses pro‐inflammatory T cells. The present study assessed the safety and efficacy of dimethyl fumarate in ALS. Methods: Phase‐2, double‐blind, placebo‐controlled randomised clinical trial recruited participants from May 1, 2018 to September 25, 2019, across six Australian sites. Participants were randomised (2:1 ratio) to dimethyl fumarate (480 mg/day) or matching placebo, completing visits at screening, baseline, weeks 12, 24 and 36. The primary efficacy endpoint was a change in Amyotrophic Lateral Sclerosis Functional Rating Scale‐Revised (ALSFRS‐R) at week 36. Secondary outcome measures included survival, neurophysiological index (NI), respiratory function, urinary neurotrophin‐receptor p75 and quality of life. Results: A total of 107 participants were randomised to dimethyl fumarate ( n  = 72) or placebo ( n  = 35). ALSFRS‐R score was not significantly different at week 36 (−1.12 [−3.75 to 1.52, p  = 0.41]). Dimethyl fumarate was associated with a reduced NI decline week 36 (differences in the least‐squares mean: (0.84 [−0.51 to 2.22, p  = 0.22]). There were no significant differences in other secondary outcome measures. Safety profiles were comparable between groups. Interpretation: Dimethyl fumarate, in combination with riluzole, was safe and well‐tolerated in ALS. There was no significant improvement in the primary endpoint. The trial provides class I evidence for safety and lack of efficacy of dimethyl fumarate in ALS.